The Discovery Learning Model on Photosynthesis Topic on Learning Outcomes and Self-Regulation of Fourth Grade Elementary School Students - Fitria Ayu Wulandari; Candra Utama; Lilik Bintartik (Jurnal Ilmiah Sekolah Dasar, 2025)
Elementary learning is expected to promote active engagement, comprehensive understanding, and self-regulation. However, students’ engagement remains suboptimal, understanding of science topics, especially photosynthesis is limited, and independent learning skills are not yet well developed. This study aims to test the effectiveness of the discovery learning model in improving student learning outcomes and self-regulation, both partially and simultaneously. This study used a quantitative approach with a quasi-experimental type and a nonequivalent control group design. The research subjects consisted of elementary school students divided into experimental and control groups. Data were collected through learning outcome tests and self-regulation questionnaires that met validity and reliability criteria. Data analysis was carried out through prerequisite tests, equivalence tests, and hypothesis tests using nonparametric and multivariate statistical techniques supported by data visualization. The results showed that the discovery learning model was more effective in improving student learning outcomes and self-regulation compared to the jigsaw cooperative learning model, both partially and simultaneously. Thus, it can be concluded that discovery learning makes a positive contribution to improving the quality of learning. The implications of this research indicate that teachers need to optimize the use of discovery learning models as a strategic alternative to encourage active involvement, conceptual understanding, and student learning independence in elementary schools.